The Effect of Problem Based Learning (PBL) Model with Analyze Case Study on Respiration System Material on Students Critical Thinking Ability - Virtanti, Uji; Lisdiana, Lisdiana; Yuniastuti, Ari (Journal of Biology Education, 2021)
Based on the results of observations at SMAN 15 Semarang students still have difficulty working on the questions requires analysis, evaluation, and a high degree of difficulty. In addition, learning has not stimulated students to improve critical thinking skills. Learning that is applied is still more dominant in the aspect of knowledge, it does not require students to be active and train thinking to find independent concepts. This study aims to analyze the effect of PBL learning by analyzing the case study material of the respiration system on students' critical thinking skills. This research was conducted at SMA N 15 Semarang with the research design Nonequivalent Control Group Design. The research steps included preliminary observation including potential and problem analysis, determining the subject as a sample, namely class XI MIPA 6 as the control class and XI MIPA 7 as the experimental class, making learning tools, compiling research instruments, conducting test questions in class XII MIPA 3, question trial analysis, research implementation, research data analysis, preparation of research results discussion. The data analysis was carried out by the prerequisite test with the normality and homogeneity test. Normality test with SPSS ver. 21 it is known that the Kolmogorov Smirnov significance criteria of 0.200> 0.05 and 0.074> 0.05 can indicate that the experimental and control classes are normally distributed. The homogeneity test shows that the Leven's significance criteria 0.163> 0.05 in both samples have the same variance. After fulfilling the prerequisite test, the two mean difference test was carried out with the test known that the significance value was 0.000 <0.05 because of the significant difference between the two samples. Then performed the N-Gain test to measure the increase in critical thinking skills. The results of the N-Gain of the experimental class in the high category were 52% and the medium category was 48%, while in the control class the moderate category was 54% and 46% low. After obtaining the N-gain, the t-test for the average N-gain score was carried out. The results of student activity in the experimental class with a higher average value in the control class. The average value of the experimental class was 83.4% in the very good category, while the control class was 75.8% in the good category. The average result of PBL implementation level with Case Study Analysis was 86.6% with very good category. Students gave very good responses to PBL learning with Case Study Analysis with an average of 83.5%. Based on these results it can ignore PBL learning with Case Study Analysis on the material of the respiration system on students' thinking abilities.